COVID-19 Survey Report II - Literacy Quebec (LQ) (2021)
While the pandemic has forced a lot of swift changes, the majority of Literacy Quebec's member organizations have been able to adapt. In fact, 8 out of 9 respondents claimed to have successfully transitioned at least some of their programs and services online. However, while most organizations were able to move to some type of online- learning model, a select few reported having no available tutors/volunteers. Some of the reasons ranged from a lack of interest (i.e. volunteers originally signed up to interact with others in person), or a lack of confidence in using technology.

Activity Report - Literacy Quebec (LQ) (2021)

Crisis Management Planning Guide - Literacy Quebec (LQ) (2021)

Crisis Management Planning - Reference Document - Literacy Quebec (LQ) (2021)

Crisis Management Planning Tool Kit - Literacy Quebec (LQ) (2021)

Family Literacy Toolkit - Literacy Quebec (LQ) (2021)